2019
DOI: 10.3390/diagnostics9030066
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Diagnosis of Primary Cutaneous Amyloidosis —The Role of Reflectance Confocal Microscopy

Abstract: Primary cutaneous amyloidosis (PCA) is a form of localized amyloidosis. It is characterized by the deposition of a fibrillar material in the superficial dermis, without affecting other systems or organs. The diagnosis can be made clinically, but usually a skin biopsy is performed in order to exclude other skin diseases with similar appearance. Reflectance confocal microscopy (RCM) is a novel imaging tool that enables in vivo characterization of various skin changes with a high, quasi-microscopic resolution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…2c, d). The results were analogous to those reported in literature [7]. DAPI staining revealed that amyloid had oval-shaped or cloud-like blue clumps of different sizes inside the der-mal papillae, which were clearly separated from the surrounding epidermis and dermal tissue (Fig.…”
Section: Histopathology and Immunofluorescence Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…2c, d). The results were analogous to those reported in literature [7]. DAPI staining revealed that amyloid had oval-shaped or cloud-like blue clumps of different sizes inside the der-mal papillae, which were clearly separated from the surrounding epidermis and dermal tissue (Fig.…”
Section: Histopathology and Immunofluorescence Performancesupporting
confidence: 90%
“…Clinical appearance differs between LA and MA: LA most commonly presents as intensely pruritic papules, sometimes coalescent with lichenification, while MA is characterized by flat hyperpigmented macules that may form a reticular or confluent pattern. These two entities cannot be clearly distinguished on the histological ground [2,6,7]. In addition, symptoms of PCA are subtle and nonspecific, often mimicking manifestations of lichenoid dermatoses, neurodermatitis, and prurigo nodularis.…”
Section: Diagnosis Of Primary Cutaneous Amyloidosis 369mentioning
confidence: 99%
“…RCM enables in vivo, non-invasive imaging of the skin layers and cellular structures in a horizontal plane at quasi-histologic resolution [11]. This imaging technique has been widely used in the diagnosis [12,13,14,15,16,17,18,19,20] and therapeutic monitoring [21,22,23,24,25] of skin cancer and inflammatory [26,27,28,29,30] and infectious skin diseases [31,32,33]. Numerous studies have investigated the diagnostic accuracy of in vivo RCM for BCC.…”
Section: Introductionmentioning
confidence: 99%
“…The RCM features of PCA have not been adequately described in the literature. Only two articles have been published to report the RCM features of PCA ( 7 , 8 ). Upon RCM, the characteristics of increased melanin in the basal cell layer, cloud-like agglomerate in the dermal papilla, and melanophage infiltrating in the layer of superficial dermis, which were corresponding to histopathological findings: basal hyper pigmentation, amyloid deposition, pigment incontinence ( 8 ).…”
Section: Discussionmentioning
confidence: 99%